Sosialisasi dan Peningkatan Kapasitas Perempuan Melalui Pelatihan Berbagai Olahan Dari Sari Pati Sagu Di Desa Huko-Huko Kecamatan Pomala Kabupaten Kolaka - I Rawati; Puji Prio Utomo; Fetni; Agusman, Yudi; Laode Asruna; Achmad Lamo Said; Ferdiansyaha (LOSARI DIGITAL, 2025)
This community service addresses the issue of local resource optimization and women's empowerment through diversification of sago starch processed products in Huko-Huko Village, Pomala District, Kolaka Regency. The objective is to enhance women's knowledge and skills in processing sago into high economic value products as an effort to strengthen food security and local economy. The implemented methods include participatory observation, socialization of sago potential, technical training on sago cracker production with modified methods, and mentoring and evaluation of production results. The outcomes demonstrate significant improvement in community understanding of the economic potential of sago, enhancement of technical skills in processing sago derivative products, and transformation of perceptions towards productive economic potential based on local commodities. This program contributes to the diversification of community income sources and strengthening of food security based on local commodities that are adaptive to local socio-ecological conditions.